P698 Mapping field cancerisation and clonal evolution in IBD colons with dysplasia and colorectal cancer. (21st January 2022) - Yalchin, M; Curtius, K; Nowinski, S; Moorghen, M; Kimberley, C; Smith, K; Baker, A M; Al-Bakir, I; Mossner, M; Nadhamuni, V; Hart, A; Graham, T
Abstract: Background: In Inflammatory Bowel Disease (IBD), clonal evolution and field cancerisation precedes the development of colitis-associated colorectal cancer (CA-CRC), however the extent and spread of pre-cancerous clones in the IBD colon remains incompletely determined and consequently clinical practice is poorly informed of how best to detect these clones by endoscopy and accurately predict future cancer risk. This study aims to quantify the number and size of mutant clones arising across the length of the colitic bowel, reveal the mechanism of how they arise and spread, and through this gain a detailed molecular understanding of the evolutionary dynamics of progression to CA-CRC. Methods: Three IBD patients undergoing a total panproctocolectomy for multifocal dysplasia or CA-CRC were recruited prospectively. Fresh-frozen biopsies were taken at regularly spaced intervals ( 2cm) across the entire colon (rectum to caecum, comprising 118, 108 and 25 biopsies respectively). Epithelial tissue was isolated from each biopsy using laser capture microdissection and DNA was extracted. Low pass whole genome sequencing (lpWGS) was performed to generate genome-wide copy number alteration (CNA) profiles. Results: Analysis from the first 45 samples from colon 1 show; 1) Multiple CNA events occur in macroscopically 'normal' parts of the colon. 2) Recurrent CNAs were shared between biopsies, revealing clonal expansions in multiple areas of the colon, both proximal and distal to the cancer, and comprising in normal, inflammed, dysplastic and cancer-adjacent tissue. 3) Clonal expansions ranged from 4-18cm in size, and were separated by distances of 2-20cm. 4) Certain CNA events occur more commonly across the colon, both independently and from within different clonal patches, such as a gain on chromosome 7 and 20, and losses on chromosomes 5, 8 and 17. 5) Whole genome doubling events within clonal clades. Conclusion: These data show that across the IBD bowel, CNAs occur and expand in ostensibly 'normal' cells, demonstrating evidence of field cancerisation. Moreover, similar CNAs are seen occurring independently throughout the whole colon, suggesting patterns of convergent evolution. Further work is needed to more precisely quantify the clonal and sub-clonal distribution across the IBD colon, in addition to deriving measures of intra-colon, intra-lesion and intra-clade genomic diversity to complement the above measures of evolvability. This data, along with the genomic-phenotypic mapping (from pending RNA analysis) and analysis of the stromal microenvironment will help demonstrate the mechanisms of CA-CRC progression and therefore help guide clinical practice through endoscopic sampling, to best predict future cancer risk.